Isopropanol at 60% and at 70% are effective against 'isopropanol-tolerant' Enterococcus faecium. Issue 1 (September 2019) - Gebel, J.; Gemein, S.; Kampf, G.; Pidot, S.J.; Buetti, N.; Exner, M.
Summary: The bactericidal activity of isopropanol was determined against Enterococcus faecium ATCC 6057, ST 796 (isopropanol-tolerant strain) and Enterococcus hirae ATCC 10541 (EN 13727). Isopropanol at 60% and 70% were effective (≥5.38 log10 -reduction) in 15 s against all strains but 23% isopropanol was not (<0.99 log10 -reduction in ≤15 min). Isopropanol at 70% was tested against E. faecium in the four-field test. Eight millilitres was not effective enough in 1 min (<5 log10 -reduction), whilst 16 mL was effective (≥5.85 log10 -reduction). Healthcare workers can be reassured that 60% and 70% isopropanol with an appropriate volume are effective against E. faecium .